ENT 530 Social Media Portfolio: Cocoa Planet / Azizah Mohamed Yusop - Mohamed Yusop, Azizah (2021)
Cocoa Planet is a small business that just started in October 2020. The business is a home-based business where our products are freshly baked and feels like home. Cocoa Planet sells soft brownie cookies and delivery services for customers, where providing variety such as classic, sea salt and white chocolate chips that aims to give high satisfaction for customer. Cocoa Planet target customer is student because, me as a student also, I always try to have some snack stored for while studying or doing assignments. Cocoa Planet also targeting families because we also provide delivery services of our product to the customer’s home and also due to current situation right now that food delivery services are progressing as people need to stay at home. Cocoa Planet marketing strategy is to fully focuses on the quality and price of the product and services we offer to customers. Cocoa Planet gives the best price for the customers because mostly of the target audience are students and they have no fixed income. I also create a Facebook page to engage with customers and learn on how to manage my business through Facebook. I need to learn on how to post and create interesting Facebook post for my business products such as seven teasers, graphics, 16 soft sell copywriting, and 16 hard sell copywriting. The requirement in the first place was to gain 99 likes for Cocoa Planet’s page and fortunately I achieved it.